Malay Graffiti In A Nineteenth-Century Lithographed Bombay Qur’an - Wieringa, Edwin (Center for Research and Development of Religious Literature and Heritage, 2018)
A lithographed copy of the Qur’ān, printed in Bombay (Mumbai, India) in 1881, was bought in Sumatra a few years later by a certain K. Bijls, a Malay-speaking Dutchman who made several markings in it which may be regarded as a form of “graffiti”, in the sense of markings asserting his ownership. This same person most probably also added a marginal calligraphic composition to the text, in a manner that is typical of Malay epistolography, perhaps prompted by an element on the printed page that was unfamiliar to him, hence catching his eye and imagination.